Часова динаміка поверхневих плазмонів - Шпількін, А. Р. (ХНУРЕ, 2022)
The excitation of surface plasmons of a metal nanowire and nanoshell by an external nonstationary source is investigated. It is shown that due to excitation by a directed pulse the resultant field has the form of an asymmetric surface wave traveling along the surface of the structure. Moreover, the distribution of the field on the surface of nanoshell is more complex, because it excites both even and odd plasmons with different Q-factors and field distributions.
Keywords: поверхневий плазмон; часова динаміка